FEATURES OF ESG MANAGEMENT DEVELOPMENT IN UZBEKISTAN - Dustova , Aziza Kakhramonovna (Educational Research in Universal Sciences, 2023)
In recent years, the trend towards responsibility and environmental friendliness has spread to the area of investment. As a result, the new concept of ESG has emerged. The article examines in detail aspects of the implementation of ESG principles in the field of business and finance, foreign and domestic experience of this phenomenon.